Development and fecundity of Reesimermis nielseni, a nematode parasite of mosquitoes - Petersen, J J (Journal of nematology, 1975)
Maturation of the mermithid nematode Reesimermis nielseni to the adult stage began by the tenth day after emergence of the nematodes from their hosts at ambient temperatures (24-27 C). Most postparasitic males and females reached the adult stage after 50 and 70 days, respectively. The first females exhibiting egg development and oviposition were observed 25-30 days after emergence, but some oviposition was still taking place 150 days later. Reesimermis nielseni laid an average 2,480 eggs per female over an 18-day oviposition period. A majority of the mature eggs hatched within 7 h after the cultures were flooded. The preparasites are short-lived, and only a few were able to infect exposed hosts after 72 h